TRANSITIVITY AND IDEOLOGY IN DONALD TRUMP CAMPAIGN SPEECH - Yuliana, Yuliana; Manda, L. M.; Darwis, Kamsinah (JURNAL ILMU BUDAYA, 2018)
Political speech is often being a topic of research in linguistic. Some of interdisciplinary studies appeared while the role of the language has developed. They are pragmatics, critical discourse analysis, phsycholingustics, neurolinguistics and sociolinguistics. This research focused on the transitivity system and ideology in Donald Trump Speech Campaign. Transitivity System that stated by Halliday become a tool to analyze the linguistic data which this theory has been used by Fairchlough in his critical discourse analysis. Based on the aims of this research that described transitivity system and ideology of Donald Trump speech campaign, therefore this research called descriptive research. Method of collecting data is method of seeing and noted technique. Technique purposive sampling is used in this research. The result showed that there are six types of process is used by Donald Trump to represent his experience, those are material process, relational process, mental process, verbal process, behavioral process, existential process. Material process is mostly used by Donald Trump followed by relational process and then mental process. To show his ideas, Donald Trump used material process mostly and showed his principal that better do action than only talk. To draw attention of US society and influenced their thought, Donald Trump is often used rasism issue in his speech campaign such as limit the access of immigrant in working and list the muslims US in separated database. Beside that, some of his statements showed that he is a narsistic. He showed his love and proud of himself mostly and he has protectionism in economy.